Rapid screening of IgG quality attributes – effects on Fc receptor binding. Issue 10 (5th September 2017) - Geuijen, Karin P. M.; Oppers‐Tiemissen, Cindy; Egging, David F.; Simons, Peter J.; Boon, Louis; Schasfoort, Richard B. M.; Eppink, Michel H. M.
Abstract : The interactions of therapeutic antibodies with fragment crystallizable γ (Fcγ) receptors and neonatal Fc receptors (FcRn) are measured in vitro as indicators of antibody functional performance. Antibodies are anchored to immune cells through the Fc tail, and these interactions are important for the efficacy and safety of therapeutic antibodies. High‐throughput binding studies on each of the human Fcγ receptor classes (FcγRI, FcγRIIa, FcγRIIb, FcγRIIIa, and FcγRIIIb) as well as FcRn have been developed and performed with human IgG after stress‐induced modifications to identify potential impact in vivo . Interestingly, we found that asparagine deamidation (D‐N) reduced the binding of IgG to the low‐affinity Fcγ receptors (FcγRIIa, FcγRIIb, FcγRIIIa, and FcγRIIIb), while FcγRI and FcRn binding was not impacted. Deglycosylation completely inhibited binding to all Fcγ receptors, but showed no impact on binding to FcRn. On the other hand, afucosylation only impacted binding to FcγRIIIa and FcγRIIIb. Methionine oxidation at levels below 7%, multiple freeze/thaw cycles and short‐term thermal/shake stress did not influence binding to any of the Fc receptors. The presence of high molecular weight species, or aggregates, disturbed measurements in these binding assays; up to 5% of aggregates in IgG samples changed the binding and kinetics to each of the Fc receptors. Overall, the screening assays described in this manuscript prove that rapid and multiplexed binding assays may be a valuable tool for lead optimization, process development, in‐process controls, and biosimilarity assessment of IgGs during development and manufacturing of therapeutic IgGs. Abstract : The binding of antibody to different classes of Fc receptors was rapidly screening in high‐throughput binding studies. Stress conditions that alter IgG and might impact its binding to Fc receptors and were rapidly identified. For example, asparagine deamidation reduces relative binding to low‐affinity Fcγ receptors, but has no impact on FcγRI and FcRn binding. Other stress conditions that were tested include: afucosylation, deglycosylation, methionine oxidation, thermal/shake stress and freeze–thaw cycles.